A COMPARATIVE STUDY BETWEEN EXTROVERT AND INTROVERT PERSONALITY OF STUDENTS SPEAKING PERFORMANCE OF UNIVERSITAS MUHAMMADIYAH BULUKUMBA - Agus Kirana Isma; Fahmi Room; Nur Ina Syam (LPPM Universitas Muhammadiyah Bulukumba, 2022)
The purpose of this research was to find out the significant difference on speaking performance between extrovert and introvert students at the sixth semester English Department of Universitas Muhammadiyah Bulukumba. The population of this study is one class in sixth semester consisting 26 students at English Department of Universitas Muhammadiyah Bulukumba. And the sample of this research were consist 5 students extrovert and 5 students introvert in 19.A class This research used quantitative approach and the type of this research was a causalcomparative. In collecting the data, the researcher distributed the questionnaire to the respondents in order to determine extrovert and introvert students, which consisted of 30 questions developed from indicators of extrovert and introvert and the questions adopted from Eysenck Personality Inventory. Then, the researcher used oral test to know students speaking performance. The researcher used analysis statistically to analyze the mean score. Then, the result of analysis statistically found that, the mean score of extrovert student is 8,2. And the mean score of introvert students is 4,8. it means that there is a significant difference on students speaking performance between extrovert and introvert students. The result showed that extrovert students outperformed than introvert students in speaking performance. Based on the finding above, it is concluded that speaking performance of extrovert students better than speaking performance of introvert students, in the sixth semseter of English Department of Universitas Muhammadiyah Bulukumba